2011
DOI: 10.1007/s11682-011-9113-8
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical brain atrophy persists even in HAART-regulated HIV disease

Abstract: The purpose of this study was to determine the pattern and extent of caudate nucleus and putamen atrophy in HIV-infected men with well-controlled immune status and viral replication. 155 men underwent structural brain magnetic resonance imaging; 84 were HIV-infected and 71 were uninfected controls. MRI data were processed using the Fully Deformable Segmentation routine, producing volumes for the right and left caudate nucleus and putamen, and 3-D maps of spatial patterns of thickness. There was significant atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
141
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(163 citation statements)
references
References 35 publications
15
141
5
Order By: Relevance
“…12 These studies found a correlation between diffuse brain atrophy and motor impairments, 10,14 dementia severity 10 and CDC stages of HIV infection, 11,13 smaller basal ganglia volume and motor dysfunction, 15 caudate and putamen atrophy and longer disease duration. 14 Similarly to these studies, we observed smaller volumes predominantly in the basal ganglia, primarily in the caudate, in HIV-positive patients with cognitive deficits. These results support the hypothesis that quantitative measures of basal ganglia volumes can be a potential biomarker for cognitive impairment assessment in these patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…12 These studies found a correlation between diffuse brain atrophy and motor impairments, 10,14 dementia severity 10 and CDC stages of HIV infection, 11,13 smaller basal ganglia volume and motor dysfunction, 15 caudate and putamen atrophy and longer disease duration. 14 Similarly to these studies, we observed smaller volumes predominantly in the basal ganglia, primarily in the caudate, in HIV-positive patients with cognitive deficits. These results support the hypothesis that quantitative measures of basal ganglia volumes can be a potential biomarker for cognitive impairment assessment in these patients.…”
Section: Discussionmentioning
confidence: 94%
“…[9][10][11][12][13] Previous studies also found smaller volumes in several specific anatomical structures, such as the basal ganglia, 9 caudate, 11,13,14 putamen, 14 and total cortex volume of HIV-positive patients. 12 These studies found a correlation between diffuse brain atrophy and motor impairments, 10,14 dementia severity 10 and CDC stages of HIV infection, 11,13 smaller basal ganglia volume and motor dysfunction, 15 caudate and putamen atrophy and longer disease duration. 14 Similarly to these studies, we observed smaller volumes predominantly in the basal ganglia, primarily in the caudate, in HIV-positive patients with cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In cART-treated patients, imaging studies associate HIV infection with shrinkage of the basal ganglia, 18 thalamus, 19 hippocampus, 20 cerebellum, 21 cortex, 22 and white matter 19 ; i.e., brain regions in which we have identified volumetric reductions related to HIV DNA. Our findings of smaller brainstem and nucleus accumbens in the pooled HIV1 and D-HIV subjects are novel.…”
mentioning
confidence: 80%
“…Indeed, neuroimaging studies within the MACS suggest that gray matter and white matter atrophy, 13 as well as subcortical atrophy in the caudate and putamen, occur in HIV1 individuals with well-controlled immune status and systemic viral replication.…”
Section: Activities Of Daily Living: the Macs Uses An Adaptation Ofmentioning
confidence: 99%